'When Theories Meet': Approaching Intergroup Contact from a Self-Determination Theory Perspective. Issue 1 (5th September 2022) - Böttcher, Johanna; Friehs, Maria-Therese
Intergroup contact theory provides a useful framework for effective interventions to improve intergroup relationship; however, disharmony between various social groups perseveres. These contact processes, their successes and failures, remain relatively unexplored from the perspective of human motivation to engage in intergroup contact. To address this, we integrate self-determination theory as a well-established theory of human motivation with existing evidence of intergroup contact research. Further, we explore the role of individual well-being in intergroup contact, which, though a prominent outcome of self-determined behavior according to motivational theories, is rarely addressed in the contact literature. Finally, this review discusses how the theoretical integration can serve to categorize and interpret findings from contact research. We deduce implications for future intergroup contact research which may reveal further mechanisms of contact and guide conceptualizing more effective intergroup contact interventions.